(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
In this work, several varieties of instant and ground, roasted black packaged coffee were studied. Various extraction methods were used to obtain extracts. The caffeine content was investigated by UV-Vis absorption spectroscopy and HPLC chromatography. The antioxidant properties of the extracts were studied by the method of competitive reactions.